Expressional STAT3/STAT5 ratio is an independent prognostic marker in colon carcinoma - Klupp, Fee; Diers, Johannes; Kahlert, Christoph; Neumann, Lena; Halama, Niels; Franz, Clemens; Schmidt, Thomas; Lasitschka, Felix; Warth, Arne; Weitz, Jürgen; Koch, Moritz; Schneider, Martin; et al. (Annals of surgical oncology, 2015)
Signal transducer and activator of transcription proteins (STATs) are crucial regulators of cell growth and differentiation; however, their specific prognostic impact in human colon cancer has only been studied to limited extent. We aimed to assess the prognostic significance of specific STAT expression patterns in colon carcinoma.
Gesehen am 10.07.2020